Evaluation and variation trend of groundwater quality in the area around Poyang Lake. Issue 1 (May 2021) - Hu, Binlong; Fu, Shasha; Zhao, Fengyao
Abstract: Aiming to study the current situation and variation trend of groundwater quality in the area around Poyang Lake, the single factor index method was used to systematically analyze 19 indicators of 242 groundwater samples in the study area. Results showed that the overall quality of groundwater in the area around Poyang Lake is poor, with Type III water accounting for 19.01 %, Type IV water accounting for 36.36 % and Type V water accounting for 44.63 %, without Type I and Type II water. The Ammonia Nitrogen index of groundwater in Poyang Lake showed a trend of improvement. The Nitrate and Sulfate index showed a trend of deterioration year by year, on the contrary. And the Hardness, Mineralization degree, Oxygen Consumption and Chloride index showed a trend of stability year by year.